1, 3, 5‐Triazine‐Functionalized Thermally Activated Delayed Fluorescence Emitters for Organic Light‐Emitting Diodes. Issue 11 (27th September 2022) - Sun, Dianming; Si, Changfeng; Wang, Tao; Zysman-Colman, Eli
Abstract : The 1, 3, 5‐triazine electron acceptor has become one of the most popular building blocks for the design of thermally activated delayed fluorescence (TADF) materials. Many TADF design strategies are first applied in compounds that contain triazines, and there are numerous examples of organic light‐emitting diodes (OLEDs) with triazine‐containing emitters that show high efficiencies and long operating lifetimes. A comprehensive review of triazine‐containing TADF emitters is provided. This review is organized according to the triazine‐derived structural motifs, such as number and position of electron‐donor groups in donor–acceptor‐type emitters, the π‐bridging linkers employed, orientation control of the transition dipole moment, and the design of chiral and through‐space charge‐transfer emitters. The structure of the compounds with their optoelectronic properties and the corresponding performance of the OLED devices is correlated. Abstract : 1, 3, 5‐Triazine is a versatile building block in thermally activated delayed fluorescence emitter design for high‐performance organic light‐emitting diodes (OLEDs). In this review, the diversity structures of trizine‐based emitters, correlate these to their photophysical properties, and the performance of the corresponding OLEDs are documented.